A Universe of Mirrors: The Mirror Metaphor in Ibn ʿArabī’s Thought in Relation to Ontology, Knowledge, and Perfection - Eletreby, Basma (AUC Knowledge Fountain, 2023)
The mirror metaphor is ubiquitous in sufi texts. It operates uniquely in Ibn ʿArabī’s thought and writings as a representation of his conception of the cosmos. Being, knowledge, and perfection are among the seminal themes of al-Shaykh al-Akbar’s thought, and the mirror metaphor is employed in revealing their reality in his writings. As opposed to Unity of Being, a term that Ibn ʿArabī does not employ, the mirror embodies the pillars of Ibn ʿArabī’s conception of Being through representing the quintessential huwa lā huwa, the configuration of oneness and manyness, and most importantly, the definition of the relation between God and the world. The mirror operates as the connective thread underlying Ibn ʿArabī’s thought. Through his concepts of the image and the ‘law of correspondence’, the role of the mirror as the configuration possibilizing knowledge, love, and perfection becomes manifest. The rather ordinary metaphor reveals the foundations of al-Shaykh al-Akbar’s thought, from rendering existence possible to accomplishing the ultimately epistemic purpose of creation.